Analisis Fungsi Bahasa Dalam Lirik Lagu Daerah Rejang “Anak Kunang” Karya Idil/Widison - Erna, Erna; Zasrianita, Fera; Wediasti, Welti (Lembaga Riset dan Inovasi Almatani, 2024)
This study aims to analyze the functions of language in the lyrics of the Rejang regional song titled